Dipole antenna with biconical and pyramidal horn design in radio frequency identification simulations - Aaron Don M. Africa; Rica Rizabel M. Tagabuhin; Jan Jayson S. D. Tirados (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Radio frequency identification (RFID) systems are used in several applications. It is widely used in retail, corporations, and schools for several purposes such as inventory, identification, and cashless payments. The components of an RFID system include a tag and a reader. The RFID reader includes an RF module that transmits and receives signals. While the RFID tag transmits embedded signals, which is typically some form of identification. The tag is a passive component powered by the reader. The two components make use of antennas to communicate the signals with each other. The design of the antenna is an important factor to consider in the production of the RFID. The size of the antenna must be small enough to provide convenience and the gain must be strong enough to effectively transmit and receive signals between the two components. In this paper, an antenna for an RFID tag is designed using MATLAB software. The antenna to be designed must be cost-efficient and be able to radiate an acceptable gain. This research creates a dipole antenna with biconical and pyramidal horn design in RFID simulations.